2017
DOI: 10.1002/ptr.5792
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Plant-derived Products in Pancreatitis: Experimental and Clinical Evidence

Abstract: Pancreatitis is a gastrointestinal disease with a worldwide sharp surge during the past decade. Pancreatitis includes acute and chronic subtypes, which are graded based on the amount of pancreatic inflammation. Phytoconstituents represent a promising class of therapeutic agents with wide acceptability not only based on folk practices but sound presence of pharmacological and molecular evidences. Growing research evidence indicates that different molecular mechanisms are involved in their protective effect. Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 251 publications
0
17
0
Order By: Relevance
“…Therefore, it is urgent to develop natural antioxidants as food additives or drugs to reduce oxidative stress. A large number of plant‐derived compounds have been explored, including polyphenols, terpenes, guanidines and flavonoids, for the treatment of a variety of pancreatic diseases, including diabetes mellitus . Vemana Gowd and the colleagues found that the antidiabetic effects of anthocyanins were attributed to their antioxidant capacity, which have been demonstrated in various organ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is urgent to develop natural antioxidants as food additives or drugs to reduce oxidative stress. A large number of plant‐derived compounds have been explored, including polyphenols, terpenes, guanidines and flavonoids, for the treatment of a variety of pancreatic diseases, including diabetes mellitus . Vemana Gowd and the colleagues found that the antidiabetic effects of anthocyanins were attributed to their antioxidant capacity, which have been demonstrated in various organ.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of plant-derived compounds have been explored, including polyphenols, terpenes, guanidines and flavonoids, for the treatment of a variety of pancreatic diseases, including diabetes mellitus. [13] Vemana Gowd and the colleagues found that the antidiabetic effects of anthocyanins were attributed to their antioxidant capacity, which have been demonstrated in various organ. Therefore, anthocyanins can be used as a potential drugs to prevent diabetes and associated complications.…”
Section: Introductionmentioning
confidence: 99%
“…Cerulein‐induced AP is a widely used model and closely resembles the human condition. A large number of phytoconstituents have been screened in this short model (Anchi et al, ). Curry leaves are natural flavoring agents and are widely used in Indian culinary recipes which gives the food an unmatched aroma.…”
Section: Discussionmentioning
confidence: 99%
“…Cerulein-induced AP is a widely used model and closely resembles the human condition. A large number of phytoconstituents have been screened in this short model (Anchi et al, 2017). (Samanta et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, cumulative clinical and experimental studies have shown that integrated traditional and Western medicine can significantly improve effectiveness (Anchi, Khurana, Bale, & Godugu, 2017). Rhubarb, as a traditional Chinese medicine, has been used for thousands of years.…”
Section: Publication Bias Analysismentioning
confidence: 99%